Young People’s Attitude and Prevention of Sexually Transmitted Infections in Institutions of Higher Learning, Machakos County, Kenya - Maingi, Ian Nzioki; Inimah, Gertrude Musuruve; Nyambane, Rhoydah (International Journal of Communication and Public Relation, 2025)
Purpose: The consequences of infection with Sexually Transmitted Diseases are a threat to populations worldwide, and especially to the youth. Young people constitute a huge part of the populace in most nations, as well as most active members of the workforce in economies. Thus, combating STIs is important for the health and development of countries. This study therefore sought to establish the influence of young people’s attitude towards prevention of STIs in Machakos County, Kenya. Methodology: The mixed methods approach was utilized to collect data from undergraduate students in three institutions of higher learning in Machakos County and from key informants, opinion leaders who interact with the young people. Findings: The study established that young people’s attitude had a great influence on prevention of STIs among the youth. Unique Contribution to Theory, Practice and Policy: The study recommended that key stakeholders should help the youth to develop positive attitudes that can yield positive outcomes in prevention of STIs among young people.